Girlhood and the Politics of Place - Mitchell, Claudia (Berghahn Books, 2016)
Examining context-specific conditions in which girls live, learn, work, play, and organize deepens the understanding of place-making practices of girls and young women worldwide. Focusing on place across health, literary and historical studies, art history, communications, media studies, sociology, and education allows for investigations of how girlhood is positioned in relation to interdisciplinary and transnational research methodologies, media environments, geographic locations, historical and social spaces. This book offers a comprehensive and authoritative reading of this emerging field and how girlhood scholars construct and deploy research frameworks that directly engage girls in the research process. This title was made Open Access by libraries from around the world through Knowledge Unlatched.